Trust me, Mom! - McAllister, Angela; Collins, Ross (New York : Bloomsbury Children$1 (Bs Books,s, 2005)
Ollie tries to be safe and polite on his first walk to the corner store alone, even when scary creatures appear on the way.
Keywords: Growth -- Fiction; Mother and child -- Fiction; Humorous stories